Prevalence of Abnormal Liver Function Tests in Celiac Disease and the Effect of a Gluten‐Free Diet in the US Population. (August 2015) - Castillo, Natalia E; Vanga, Rohini R; Theethira, Thimmaiah G; Rubio‐Tapia, Alberto; Murray, Joseph A; Villafuerte, Javier; Bonder, Alan; Mukherjee, Rupa; Hansen, Joshua; Dennis, Melinda; Kelly, Ciaran P; Leffler, Daniel A
Abstract : OBJECTIVES: Guidelines recommend routine screening of liver function tests (LFTs) in patients diagnosed with celiac disease (CD). However, little is known about the prevalence of liver disorders in CD outside of Europe. Our aims were to estimate the prevalence of LFT abnormalities in CD and to evaluate the effect of a gluten‐free diet (GFD) on LFTs. METHODS: Adult patients with biopsy‐proven CD were identified from a prospectively maintained database and matched with healthy controls. LFT levels for women and men were defined as abnormal based on the Third National Health and Nutrition Examination Survey (NHANES III) criteria. Data on demographics, coexisting liver diseases, and laboratory work‐ups including aspartate transaminase (AST) and alanine transaminase (ALT) values at the time of diagnosis and on a GFD were recorded. Subsequently, data from this cohort were compared with data from 7, 789 individuals participating in the National Health and Nutrition Examination Survey, 2009–2010. Univariate logistic regression, Wilcoxon signed‐ranks, Student's t ‐test, χ 2, and Fischer's exact test were used for statistical analysis. RESULTS: In 463 CD patients with ALT or AST levels at the time of CD diagnosis, 40.6% had elevated LFTs compared with 24.2% of treated CD patients ( P <0.001) and 16.6% of matched controls ( P <0.001). Similarly, 36.7% of CD patients on the NHANES database had abnormal ALT values compared with 19.3% of non‐celiac patients ( P =0.03). Approximately, 78.6% of CD patients with elevated LFTs at diagnosis normalized LFTs on a GFD after a mean duration of 1.5±1.5 years. CONCLUSIONS: Forty percent of individuals will have elevated LFTs at CD diagnosis; however, the majority will normalize with standard CD therapy. LFTs should be checked in all patients with CD and coexisting liver disorder should be considered in patients whose LFTs have not improved within a year on a GFD.